{Microorganisms Associated with the Marine Sponge Scopalina hapalia: A Reservoir of Bioactive Molecules to Slow Down the Aging Process} - Said Hassane, Charifat; Fouillaud, Mireille; Le Goff, Géraldine; Sklirou, Aimilia D.; Boyer, Jean Bernard; Trougakos, Ioannis P.; Jerabek, Moran; Bignon, Jérôme; de Voogd, Nicole J.; Ouazzani, Jamal; Gauvin-Bialecki, Anne; Dufossé, Laurent (Microorganisms, 2020)
Aging research aims at developing interventions that delay normal aging processes and some related pathologies. Recently, many compounds and extracts from natural products have been shown to delay aging and/or extend lifespan. Marine sponges and their associated microorganisms have been found to produce a wide variety of bioactive secondary metabolites; however, those from the Southwest of the Indian Ocean are much less studied, especially regarding anti-aging activities. In this study, the microbial diversity of the marine sponge Scopalina hapalia was investigated by metagenomic analysis. Twenty-six bacterial and two archaeal phyla were recovered from the sponge, of which the Proteobacteria phylum was the most abundant. In addition, thirty isolates from S. hapalia were selected and cultivated for identification and secondary metabolites production. The selected isolates were affiliated to the genera Bacillus, Micromonospora, Rhodoccocus, Salinispora, Aspergillus, Chaetomium, Nigrospora and unidentified genera related to the family Thermoactinomycetaceae. Crude extracts from selected microbial cultures were found to be active against seven targets i.e., elastase, tyrosinase, catalase, sirtuin 1, Cyclin-dependent kinase 7 (CDK7), Fyn kinase and proteasome. These results highlight the potential of microorganisms associated with a marine sponge from Mayotte to produce anti-aging compounds. Future work will focus on the isolation and the characterization of bioactive molecules.
Keywords: Actinomycetes; Bacillus; Catalase activation; CDK7 inhibition; Elastase inhibition; Fungi; Fyn kinase inhibition; Scopalina hapalia; Sirtuin 1 activation; Tyrosinase inhibition